2005
DOI: 10.1016/s0031-3203(04)00185-2
|View full text |Cite
|
Sign up to set email alerts
|

Illuminant and device invariant colour using histogram equalisation

Abstract: Colour can potentially provide useful information for a variety of computer vision tasks such as image segmentation, image retrieval, object recognition and tracking. However, for it to be helpful in practice, colour must relate directly to the intrinsic properties of the imaged objects and be independent of imaging conditions such as scene illumination and the imaging device. To this end many invariant colour representations have been proposed in the literature. Unfortunately, recent work (Second Workshop on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 5 publications
0
41
0
Order By: Relevance
“…where o and c represent different illumination conditions and a; b and c are diagonal coefficients which indicate the relationship between o and c illumination conditions (Finlayson, Hordley, Schaefer, & Tian, 2005). The rank order is preserved under the change of illumination and following relation can be derived as follows:…”
Section: White Lane Marking Detectionmentioning
confidence: 99%
“…where o and c represent different illumination conditions and a; b and c are diagonal coefficients which indicate the relationship between o and c illumination conditions (Finlayson, Hordley, Schaefer, & Tian, 2005). The rank order is preserved under the change of illumination and following relation can be derived as follows:…”
Section: White Lane Marking Detectionmentioning
confidence: 99%
“…The mean percentage of such pairs of corresponding pixels reaches 55%. We have shown, in a previous work, that another assumption which stipulates that the rank measures of corresponding pixels are preserved across illumination changes (Finlayson et al, 2005) has been only verified for 6% of corresponding pixels in the three similar color images of Fig. 1 (Muselet et al, 2005).…”
Section: Closest Interval Assumptionmentioning
confidence: 81%
“…Funt has tested several invariant features on the database of the Simon Fraser University (SFU) and has demonstrated that the object recognition results obtained by the intersection between the invariant histograms processed by the greyworld normalization outperforms those obtained by the intersection between classical invariant histograms (Funt et al, 1998). Furthermore, Finlayson have used the East Anglia University (EAU) database and has concluded that the intersection between the invariant histograms resulting from one-dimensional histogram equalization provides better results than those obtained by greyworld normalization (Finlayson et al, 2003). Hence, we propose to use these two databases and to compare the results obtained by these two schemes with those obtained by the mean intersection between the adapted co-occurrence matrices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations